ANALISIS KINERJA PEGAWAI DALAM KONTEK PENERAPAN ONLINE SYSTEM PADA UNIVERSITAS ISLAM RIAU DI PEKANBARU - Arief Rifa’i Harahap; Lilis Suriani; Rosmita Rosmita (UIR Press, 2017)
This study takes the theme of employee performance analysis in the context of online system implementation at the Islamic University of Riau in Pekanbaru City. Islamic University of Riau, is one of Islamic Education Institution that is undergoing the development of transformation in the implementation of information technology. Since formulated in the company policy in 2014 to implement student administration system based on information technology. information-based information and communication technology system, namely online system, in response to the problems faced to increase competitiveness and improve the quality of service to various parties. Academic Information System, abbreviated as 'Academic system', is an online-based information system service for students who function as a means to fill out Study Plan Card (Study Plan Card), print Study Study Card (card of study results), and print Value Transcript. The Academic system system is enforced throughout 2014 for all classes. Constraints related to human resource factors. These constraints include (1) relatively slow transfer of knowledge, (2) employees who are poorly trained in training, (3) employees are less enthusiastic to follow changes in information technology applied by the organization, (4) when employee turnover, still not ready, because the different task demands in the use of information technology in a new position. From the results of this study can be concluded that the performance of employees in the perception of quantity of work, quality of work, work knowledge, and timeliness in the context of the online system application (Academic system) that since the implementation of online system (Academic system) has a good influence while the performance of employees in perception work skills in the context of online system implementation (Academic system) has a pretty good influence.